Minimally Invasive Treatment of Chyle Leak After Thyroidectomy and Cervical Lymph Node Dissection in Patients with Thyroid Carcinoma: Results of a Study Involving 36 Patients - Cuong NN; Hoan L; Tra My TT; Luu DT; Tuan Linh L; Canh PH; Tinh TQ; Khanh Chi TN; Trung NQ; Hoa TQ (Dove Medical Press, 2024)
Nguyen Ngoc Cuong,1,* Le Hoan,2,* Thieu Thi Tra My,3 Doan Tien Luu,1 Le Tuan Linh,1 Pham Hong Canh,1 Trieu Quoc Tinh,1 Tran Nguyen Khanh Chi,1 Nguyen Quang Trung,1 Tran Quoc Hoa4 1Diagnostic Imaging and Interventional Center, Hanoi Medical University Hospital, Ha Noi, Viet Nam; 2Respiratory Department, Hanoi Medical University Hospital, Ha Noi, Viet Nam; 3Diagnostic Imaging and Nuclear Medicine Department, Vinmec Times City International Hospital, Ha Noi, Viet Nam; 4Urology Surgery department, Hanoi Medical university, Ha Noi, Viet Nam*These authors contributed equally to this workCorrespondence: Nguyen Ngoc Cuong, Diagnostic Imaging and Interventional Center, Hanoi Medical University Hospital, No. 1, Ton That Tung, Dong Da, Ha Noi, Viet Nam, Email Cuongcdha@gmail.comObjective: Chyle leak (CL) after head and neck surgery is a rare but well-known complication. In patients with high-output leakage, the treatment can be complicated. This study aims to report on a recent innovation in lymphatic intervention for treating such patients.Materials and Methods: A retrospective review of 36 patients with chyle leak after neck surgery for thyroid cancer was conducted to assess the efficacy of percutaneous lymphatic embolization and thoracic duct (TD) disruption.Results: Antegrade catheterization of the thoracic duct was achieved in 31 of 36 patients (86.1%). Therefore, embolization of the thoracic duct and thoracic duct branches was performed in 26 and 5 patients, respectively. In 5 cases of unsuccessful antegrade catheterization into the thoracic duct, transcervical access embolization was performed in 2 patients, and TD disruption (TDD) was performed in 3 patients. The pooled overall technical success rate of lymphatic embolization was 33/36 patients (91.7%). One patient who underwent thoracic duct embolization (TDE) with technical success (1/33 patients) but clinical failure had additional treatment directly sclerosing the TD under computed tomography scan. Cervical fluid collection sclerotherapy was done in 7 patients as an additional treatment. Resolution of the chyle leak after procedures was observed in all patients (100%). The mean time to resolution was 3 days (1- 7 days). There was no complication intra and after procedures.Conclusion: TDE, selective TD branches embolization and TDD are safe and effective minimally invasive treatments for CL post-surgery for thyroid carcinoma. Sclerosing cervical fluid collection contributes to clinical success.Keywords: thyroid cancer, thyroidectomy, chyle leak, thoracic duct embolization, thoracic duct disruption, sclerotherapy